Unemployment insurance: a social rescue policy in the face of the labor consequences of the pandemic in Guatemala. - Velásquez Pérez, Luis Guillermo (Política. Revista de Ciencia Política, 2023)
The emergence of the Covid-19 pandemic forced the implementation of confinement and mobility restriction measures that affected jobs around the world. In the Guatemalan case, they also revealed a series of historical failures and weaknesses within the labor institution. In this sense, this article investigates based on data from 2020, the viability of implementing unemployment insurance administered by the Guatemalan Social Security Institute, an achievement of the revolutionary decade (1944-1954), as an immediate and long-term policy for recovery. economic, protection against unemployment and improving the search for jobs.